Student Psychology Prediction and Recommendation System Using Rough Set Theory - Ratnaparkhi, Bhakti; Katore, Lokesh; Umale, JS; Upadhyay, Niharika (International Journal of Computer Sciences and Engineering, 2015)
Big data analysis includes many theories and methods for prediction system. Statistical methods such as Person’s correlation, Regression analysis and Rough Set Theory etc are being used for predicting facts. Also theory like collaboration filtering uses word’s filtering to predict and provide recommendations. We have studied all these methods and selected most appropriate method for student’s psychology prediction. In our proposed work we have used Rough sets to extract the rules for prediction of student’s psychology. Rough Set is a comparatively recent method that has been effective in various fields such as medical, geological and other fields where intelligent decision making is required. Our experiments with rough sets in predicting student’s psychology produced attractive results.